One last word : a novel - Park, Suzanne (Avon, an imprint of HarperCollinsPublishers, 2024)
The founder of the One Last Word app, which allows you to send messages to whomever you want after you pass, Sara Chae, when she accidentally sends her final words to the important people in her life, including her former crush, with whom she now works, finds her life turned upside down.